Communication—Selective Adsorption of PEG on SiO2 for High Removal Selectivity in Tungsten CMP. (6th March 2018) - Kim, Kijung; Lee, Kangchun; So, Sounghyun; Cho, Sungwook; Lee, Myeongjae; You, Keungtae; Moon, Jinok; Song, Taeseup
Abstract : We studied the effect of selective adsorption of polyethylene glycol (PEG) on SiO2 for high removal selectivity of tungsten to SiO2 in tungsten CMP. The hydrogen bonding between PEG and SiO2 increased as the solution pH decreased. At pH 3, the maximum adsorption of PEG on SiO2 occurred due to the low surface charge of SiO2 (near its isoelectric point). The selective adsorption led to the selective reduction of removal rate of SiO2 during CMP process. As a result, the removal selectivity increased from 4.5 to 85.5 as the PEG concentration increased from 0 to 9 wt% at pH 3.